Pellagra, then and now - Viljoen, Margaretha; Claassen, Nicolaas (Medicina Historica, 2022)
By the mid-20th century, pellagra had virtually been eradicated from the USA and Europe. Eradication of the disease on the African continent lags behind. Outbreaks are maintained by escalating food insecurity, violent unrest and possibly by the burden of communicable diseases.